Can an airway assessment score predict difficulty at intubation in the emergency department?. Issue 2 (20th January 2005) - Reed, M J; Dunn, M J G; McKeown, D W
Abstract : Aim: To assess whether an airway assessment score based on the LEMON method is able to predict difficulty at intubation in the emergency department. Methods: Patients requiring endotracheal intubation in the resuscitation room of a UK teaching hospital between June 2002 and September 2003 were assessed on criteria based on the LEMON method. At laryngoscopy, the Cormack and Lehane grade was recorded. An airway assessment score was devised and assessed. Results: 156 patients were intubated during the study period. There were 114 Cormack and Lehane grade 1 intubations, 29 grade 2 intubations, 11 grade 3 intubations, and 2 grade 4 intubations. Patients with large incisors (p<0.001), a reduced inter-incisor distance (p<0.05), or a reduced thyroid to floor of mouth distance (p<0.05) were all more likely to have a poor laryngoscopic view (grade 2, 3, or 4). Patients with a high airway assessment score were more likely to have a poor laryngoscopic view compared with those patients with a low airway assessment score (p<0.05). Conclusions: An airway assessment score based on criteria of the LEMON method is able to successfully stratify the risk of intubation difficulty in the emergency department. Patients with a poor laryngoscopic view (grades 2, 3, or 4) were more likely to have large incisors, a reduced inter-incisor distance, and a reduced thyroid to floor of mouth distance. They were also more likely to have a higher airway assessment score than those patients with a good laryngoscopic view.